Classification and integration of knowledge: the Qur’anic educational model - Surajudeen, Ahmad Tijani; Awang Mat , Muhamad Zahiri (2013)
The contemporary Muslims have been swimming in the ocean of dilemma and confusion. Disunity, disintegration between religious and non-religious knowledge integrally and immensely contributed to this dilemma. The scriptural manual of guidance, the Quran has been neglected from being the basis of educational policy and curriculum among a vast majority of Muslims. Several studies have posited that for Muslims to get rid these challenges, their educational system must be formulated on the basis of the Qur’anic paradigm and unification of educational system must be formulated on the basis of the Qur’anic paradigm and unification of religious sciences (ilm naqli) and non-religious sciences (ilm aqli). Various scholarly studies have examined the classical works on the classification and integration of religious and non-religious knowledge among the contemporary Muslims by considering the Qur’anic model and tawhidic paradigm. This paper primarily aims at examining the classification and integration of knowledge from the Qur’anic model. Accordingly, the scriptural book, chapter 62 verse 2 will be critically analyzed. The paper is library-based whereby both primary and secondary sources will be extensively analyzed. The epistemological and philosophical issues relating to the classification and integration of knowledge will be also explicitly elaborated. The finding from the Qura’anic model of Classification and integration of knowledge with particular reference to Q62:2 identified three divisions of knowledge namely: religious, pure and natural sciences in relation to the sign (ayaatu manzhur and ayaatu mantuq) which form the epistemological foundation of Qur’anic and tawhidic paradigm of integration of knowledge among the contemporary Muslims. It s thereby recommended that, for Muslims to revive the intellectual success of classical Islamic civilization and contributions of Muslims scholars to knowledge, it is essential paramount to be cognizance of creative ideas embodied in the Holy Qur’an.